Factors Related to Dermatitis Contact with Fishers at Oeba Fish Market, Kupang City - Syafaatu Mizzannati Syari; Anderias Umbu Roga; Agus Setyobudi (Media Kesehatan Masyarakat, 2022)
Skin disorders have been identified as significant health problems in the marine environment. Occupational skin diseases that usually arise are dermatitis problems that cause contact irritants or allergies. Fishermen are people capturing fish in the sea, and they are at risk of getting skin diseases, namely dermatitis, which is an environmentally-based skin disease. The study purpose is to determine and analyse factors associated with irritant contact dermatitis among fishermen at Oeba Fish Market, Kupang City. This research used analytical methods with a cross-sectional design. The population was 120 fishermen working at Oeba Fish Market. A total of 92 fishermen was selected as sample using simple random sampling. Data were analysed using univariate and bivariate analysis with the Chi−Square test. The results showed that personal hygiene, personal protective equipment usage and period of work with irritant contact dermatitis where the p-value<α (0.05). There was no relationship found between duration of contact and irritant contact dermatitis where the p-value>α (0.05). Fishermen should use complete personal protective equipment during the work process, especially gloves, work clothes and work shoes to prevent direct contact and also pay attention to personal hygiene while working.